Peranan Psikologi dalam Pengembangan Sikap Positif Belajar Peserta Didik - Sholeh Widodo; Wa Ode Yesi Gusman; Rinawati Tiflen; Prihaten Maskuliah (Journal Innovation In Education, 2025)
This article explores the role of psychology in shaping positive learning attitudes in students. Learning attitudes are influenced by various psychological factors that interact with each other and impact the way students approach learning. Understanding how these psychological components relate can assist educators in fostering motivation and positive attitudes among learners. The article highlights the importance of motivation as a key element in developing a constructive learning attitude. By providing effective motivation, educators can strengthen students' positive attitudes toward their learning activities.